2007
DOI: 10.1016/j.ygyno.2007.08.060
|View full text |Cite
|
Sign up to set email alerts
|

Serum CA125 predicts extrauterine disease and survival in uterine carcinosarcoma

Abstract: Objective-The purpose of this study was to determine the clinical utility of CA125 measurement in patients with uterine carcinosarcoma (CS).Methods-Ninety-five consecutive patients treated for CS at a single institution were identified. All 54 patients who underwent preoperative CA125 measurement were included in the study. Data were abstracted from the medical records. Tests of association between preoperative CA125 and previously identified clinicopathologic prognostic factors were performed using Fisher's e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 34 publications
1
36
1
1
Order By: Relevance
“…The presenting symptom of this neoplasm often was abnormal uterine bleeding in post-menopause (40.9%) [15] , even if the patients frequently were asymptomatic (54.5%) [21] . In the literature [22] increased CA-125 serum levels have also been reported to be associated with the disease. In our study we found 18.2% patients with an increased CA-125 level.…”
Section: Discussionmentioning
confidence: 98%
“…The presenting symptom of this neoplasm often was abnormal uterine bleeding in post-menopause (40.9%) [15] , even if the patients frequently were asymptomatic (54.5%) [21] . In the literature [22] increased CA-125 serum levels have also been reported to be associated with the disease. In our study we found 18.2% patients with an increased CA-125 level.…”
Section: Discussionmentioning
confidence: 98%
“…For example, in a retrospective study of 54 patients, a CA-125 value above 30 U/ml was significantly associated with deep myometrial invasion (61% vs. only 39% in patients with CA-125 below 30 U/ml) as well as higher disease stage (62% vs. only 38%) [8]. …”
Section: Diagnosismentioning
confidence: 99%
“…In this study, the preoperative detection of the serum CA125 level was performed only in 43 patients (57.3%), and in patients with stage III and IV disease, the mean CA125 level was higher than in patients with stage I disease. A significantly elevated preoperative CA125 level was associated with the presence of extrauterine disease and late disease stage [16]. However, the majority of late stage cases did not exhibit preoperative elevated CA125 levels.…”
Section: Ultrasonographic Characteristicsmentioning
confidence: 87%
“…More recently, the potential utility of CA125 measurement has been evaluated in endometrial cancer patients. Several investigators have found that elevated levels of preoperative CA125 in patients with endometrial cancer (including UCS) are associated with pathologic risk factors such as high tumor grade, deep myometrial invasion, lymphovascular involvement, extrauterine disease, and nodal metastases [16][17][18]. In this study, the preoperative detection of the serum CA125 level was performed only in 43 patients (57.3%), and in patients with stage III and IV disease, the mean CA125 level was higher than in patients with stage I disease.…”
Section: Ultrasonographic Characteristicsmentioning
confidence: 99%